2012
DOI: 10.5194/acp-12-2747-2012
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties, morphology and elemental composition of atmospheric particles at T1 supersite on MILAGRO campaign

Abstract: Atmospheric particles were sampled at T1 supersite during MILAGRO campaign, in March 2006. T1 was located at the north of Mexico City (MC). Aerosol sampling was done by placing copper grids for Transmission Electron Microscope (TEM) on the last five of an 8-stage MOUDI cascade impactor. Samples were obtained at different periods to observe possible variations on morphology. Absorption and scattering coefficients, as well as particle concentrations (0.01–3 μm aerodynamic diameter) were measured simultaneously u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…This enhanced absorption in such structure is because of the lensing effect of coated materials (Jacobson, 2001). Field measurements indicate that during transport from the sources, fresh soot becomes internally mixed with sulfate and organics, leading to enhancement in light absorption, which was in agreement with the results of modelling calculation Doran et al, 2007;Carabali et al, 2012). Kleinman et al (2007) observed a doubling in the ratio of aerosol light absorption in aged air masses compared to fresh emissions over the eastern US.…”
Section: Introductionsupporting
confidence: 78%
“…This enhanced absorption in such structure is because of the lensing effect of coated materials (Jacobson, 2001). Field measurements indicate that during transport from the sources, fresh soot becomes internally mixed with sulfate and organics, leading to enhancement in light absorption, which was in agreement with the results of modelling calculation Doran et al, 2007;Carabali et al, 2012). Kleinman et al (2007) observed a doubling in the ratio of aerosol light absorption in aged air masses compared to fresh emissions over the eastern US.…”
Section: Introductionsupporting
confidence: 78%
“…This enhanced absorption in such structure is because of the lensing effect of coated materials (Jacobson, 2001). Field measurements indicate that during transport from the sources, fresh soot becomes internally mixed with sulphate and organics, leading to enhancement in light absorption, which confirms the modelling calculation (Kleinman et al, 2007;Doran et al, 2007;Carabali et al, 2012). Kleinman et al observed a doubling in the ratio of aerosol light absorption in aged air masses compared to fresh emissions over the eastern U.S. (Kleinman et al, 2007).…”
Section: Introductionmentioning
confidence: 66%
“…The AOD parameter measured by the Aerosol Robotic Network (AERONET) represents the vertically integrated extinction coe cient in the atmospheric column. Simultaneous analyzes of the aerosol morphological properties and their elemental composition is an alternative to characterize them 2,[16][17][18][19] . While particle shape can be associated with their size and optical properties, the elemental composition is related to their origin and mixing state.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their composition and morphology, urban aerosol particles can be classi ed as soot, tarballs (TB), mineral dust, S-rich and K-rich, sea salt, metallic, among others [20][21][22] . This classi cation can be performed by using Transmission-(TEM) and Scanning electron microscopy (SEM) techniques coupled with the energy dispersed X-ray detector (EDX or EDS) 19,20,23 .…”
Section: Introductionmentioning
confidence: 99%